Evidence that v-src and v-fps gene products use a protein kinase C-mediated pathway to induce expression of a transformation-related gene. - Spangler, R (1989)
Induction of the transformation-related gene 9E3 by the v-src and v-fps gene products (v-Src and v-Fps) is blocked in chicken embryo fibroblasts depleted of protein kinase C (PKC). PKC agonists induce 9E3 gene expression. Protein kinase inhibitors block v-Src- and v-Fps-induced 9E3 gene expression with the same dose-response curves seen for PKC agonist-induced 9E3 gene expression. These data suggest that v-Src and v-Fps use a PKC-mediated signal-transduction pathway to induce expression of the transformation-related 9E3 gene. Consistent with this hypothesis, we find that both v-Src and v-Fps rapidly induce phosphorylation of a 67-kDa PKC substrate.